2015
DOI: 10.1111/mcn.12214
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of micronutrient powder sachet coverage in Nepal

Abstract: Many countries implement micronutrient powder (MNP) programmes to improve the nutritional status of young children. Little is known about the predictors of MNP coverage for different delivery models. We describe MNP coverage of an infant and young child feeding and MNP intervention for children aged 6–23 months comparing two delivery models piloted in rural Nepal: distributing MNPs either by female community health volunteers (FCHVs) or at health facilities (HFs). Cross-sectional household cluster surveys were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 17 publications
11
58
1
Order By: Relevance
“…The vast majority of published papers report on evaluations in the context of a pilot project (Creed‐Kanashiro, Bartolini, Abad, & Arevalo, 2015; Harris et al, 2012; Jefferds et al, 2015; Korenromp et al, 2015; Loechl et al, 2009; Mirkovic, Perrine, Subedi, Mebrahtu, Dahal, & Jefferds, 2016; Mirkovic, Perrine, Subedi, Mebrahtu, Dahal, Staatz, et al, 2015; Nguyen et al, 2016; Suchdev et al, 2010, 2013; Sun et al, 2011), with the exception of Bangladesh which reports on national programmes (Afsana, Haque, Sobhan, & Shahin, 2014; Angdembe, Choudhury, Haque, & Ahmed) and three large‐scale MNP distribution in refugee camps and in emergency contexts (de Pee et al, 2007; Kodish, Rah, Kraemer, de Pee, & Gittelsohn, 2011; Rah et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of published papers report on evaluations in the context of a pilot project (Creed‐Kanashiro, Bartolini, Abad, & Arevalo, 2015; Harris et al, 2012; Jefferds et al, 2015; Korenromp et al, 2015; Loechl et al, 2009; Mirkovic, Perrine, Subedi, Mebrahtu, Dahal, & Jefferds, 2016; Mirkovic, Perrine, Subedi, Mebrahtu, Dahal, Staatz, et al, 2015; Nguyen et al, 2016; Suchdev et al, 2010, 2013; Sun et al, 2011), with the exception of Bangladesh which reports on national programmes (Afsana, Haque, Sobhan, & Shahin, 2014; Angdembe, Choudhury, Haque, & Ahmed) and three large‐scale MNP distribution in refugee camps and in emergency contexts (de Pee et al, 2007; Kodish, Rah, Kraemer, de Pee, & Gittelsohn, 2011; Rah et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…MNP has been locally branded in Nepal as Baal Vita (translated as “Vitamins for Children”); each sachet contains 15 micronutrients including iron and zinc at ~1x the Recommended Nutrient Intake (WFP/WHO/UNICEF, ). After a feasibility study assessed the acceptability of MNP and developed key messages and strategies for the integrated IYCF‐MNP programme, a pilot programme was conducted in 2010–2011 where MNP was delivered in some districts through government‐run health facilities and in other districts through female community health volunteers (FCHVs; Jefferds et al, ). Beginning in late 2012, the Ministry of Health and the United Nations Children's Fund (UNICEF) began scaling‐up the integrated IYCF‐MNP programme, which as of 2016 had reached 26 out of the country's 75 districts.…”
Section: Methodsmentioning
confidence: 99%
“…The free health sector MNP programmes, which usually distribute MNP through routine health facility visits, health facility visits and community outreach, or biannual child health days, have coverage rates ranging from 32% to 83% based on each programme's definition of coverage (Jefferds et al, ; Korenromp et al, ; Reerink et al, ), and intake adherence (defined by each programme) of 35–88% (Jefferds et al, ; Korenromp et al, ; Reerink et al, ; World Vision, ). Notably, the majority of evaluations reporting coverage and intake data have come from pilot interventions in small areas with more resources than would be available during national or subnational implementation (Jefferds et al, ; Korenromp et al, ; Reerink et al, ; World Vision, ). A recent MNP expert consultative group concluded that implementation research from programmes operating at scale (defined as reaching a large population with long‐term delivery infrastructure) is urgently needed to inform MNP programmes globally (Nyhus Dhillon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Longer‐term use was better in the FCHV model, but the FCHVs reported increased work burden, which should be addressed as the programme is scaled‐up (Jefferds et al . ).…”
Section: Monitoring Programme Implementationmentioning
confidence: 97%
“…; Jefferds & Flores‐Ayala ; Jefferds et al . ; Osei et al . ) fortified complementary food (Bauserman et al .…”
mentioning
confidence: 99%